The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2042018820906016
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-delivery methods for children and adolescents with type 1 diabetes

Abstract: Efforts directed toward restoring normal metabolic levels by mimicking the physiological insulin secretion, thereby ensuring safety, efficacy, minimal invasiveness and conveniences, are of great significance in the management of type 1 diabetes among children and adolescents. Regardless of the various technologies being discovered in addressing invasiveness and enhancing medication adherence in the management of type 1 diabetes, yet limited success had been observed among children and adolescents. The multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…As regard method of insulin injection, the present study illustrated that, the majority of the studied children used insulin syringes this may be due to the insulin pump or pen aren't available for all diabetic children or may cause financial load for parents. This finding wasn't in harmony with Zuberi et al (2020) (38) who studied insulin-delivery methods for children and adolescents with type 1 diabetes and his study revealed that, the diabetic alternate delivery method for children and adolescents is insulin pens. Concerning to frequency of insulin injections, the current study revealed that, all the studied children taken insulin injection four times per day.…”
Section: Discussionmentioning
confidence: 81%
“…As regard method of insulin injection, the present study illustrated that, the majority of the studied children used insulin syringes this may be due to the insulin pump or pen aren't available for all diabetic children or may cause financial load for parents. This finding wasn't in harmony with Zuberi et al (2020) (38) who studied insulin-delivery methods for children and adolescents with type 1 diabetes and his study revealed that, the diabetic alternate delivery method for children and adolescents is insulin pens. Concerning to frequency of insulin injections, the current study revealed that, all the studied children taken insulin injection four times per day.…”
Section: Discussionmentioning
confidence: 81%
“…The typical signs are persistent hunger, frequent urination, and extreme thirst. In those who are genetically susceptible to type II diabetes, obesity is now understood to be the root cause of the condition [30,31] . α‐Glucosidase inhibitors are used in conjunction with other insulin secretagogues to maintain high glycemic control [32,33] .…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme is also located in the lining of small intestine where it plays a crucial role in the final stage of glucose metabolism. The enzyme functions by catalyzing the α-glucosidic disaccharide and oligosaccharide bonds owing to the presence of duplicated glycoside hydrolase domains (GH31). , Besides carbohydrate digestion, α-glucosidase enzyme is also essential for numerous biological processes such as degradation of lysosomal glycoconjugates and the modification of post-translational glycoproteins . The enzymatic activity of α-glucosidase is significant in the management of type 2 diabetes mellitus (T2DM) as its inhibition retards the rate of breakdown of starch.…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 Besides carbohydrate digestion, α-glucosidase enzyme is also essential for numerous biological processes such as degradation of lysosomal glycoconjugates and the modification of post-translational glycoproteins. 26 The enzymatic activity of α-glucosidase is significant in the management of type 2 diabetes mellitus (T2DM) as its inhibition retards the rate of breakdown of starch. It helps in regulating the postprandial hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%